Epidemiological study using IgM and IgG antibody titers against SARS-CoV-2 in The University of Tokyo, Japan (UT-CATS). Issue 9 (September 2021) - Mitani, Akihisa; Hamada, Kensuke; Yoshikawa, Naoyuki; Morita, Yoshifumi; Horie, Takeshi; Inoue, Yukiko; Saito, Minako; Ishii, Takashi; Sunohara, Mitsuhiro; Takahashi, Ryota; Emoto, Noriko; Nishimoto, Nahoko; et al.
Abstract: Introduction: The worldwide pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has continued to date. Given that some of the patients with coronavirus disease 2019 (COVID-19) are asymptomatic, antibody tests are useful to determine whether there is a previous infection with SARS-CoV-2. In this study, we measured IgM and IgG antibody titers against SARS-CoV-2 in the serum of asymptomatic healthy subjects in The University of Tokyo, Japan. Methods: From June 2020, we recruited participants, who were students, staff, and faculty members of The University of Tokyo in the project named The University of Tokyo COVID-19 Antibody Titer Survey (UT-CATS). Following blood sample collection, participants were required to answer an online questionnaire about their social and health information. We measured IgG and IgM titers against SARS-CoV-2 using iFlash-SARS-CoV-2 IgM and IgG detection kit which applies a chemiluminescent immunoassay (CLIA) for the qualitative detection. Results: There were 6609 volunteers in this study. After setting the cutoff value at 10 AU/mL, 32 (0.48%) were positive for IgG and 16 (0.24%) for IgM. Of six participants with a history of COVID-19, five were positive for IgG, whereas all were negative for IgM. The median titer of IgG was 0.40 AU/mL and 0.39 AU/mL for IgM. Both IgG and IgM titers were affected by gender, age, smoking status, and comorbidities. Conclusions: Positive rates of IgG and IgM titers were relatively low in our university. Serum levels of these antibodies were affected by several factors, which might affect the clinical course of COVID-19.